PENGARUH SUBSTITUSI TEPUNG KEDELAI DENGAN TEPUNG LEMNA TERFERMENTASI TERHADAP PERTUMBUHAN NILA MERAH (Oreochromis sp.) - Put Pilihan Kinayungan; Senny Helmiati (Journal of Fish Nutrition, 2021)
Lemna has a fairly good protein content. The use of Lemna as a fish feed material is experiencing obstacles such as materials derived from plants in general, namely low protein levels and high levels of fiber. This study aims to find out the nutrient content of fermented Lemna meal and the effect of fermented Lemna meal on the growth of red indigo (Oreochromis sp.). The study used the Complete Randomized Design Method with four dose treatments: P0 (0%), P1 (10%), P2 (20%), and P3 (30%) with three repeats. The study used red tilapia measuring 7-9 cm and was maintained for 60 days. Feed is given as much as 3% of fish biomass with the frequency of feeding twice a day. Fermented Lemna meal has a water content of 4.45±0.07%, protein by 13.67±0.08%, fat by 4.24±0.81%, ash by 26.9±0.14%, fiber by 32.53±0.29%, and carbohydrates by 50.74±0.81%. Fermentation can increase protein levels from Lemna. Substitution of soybean meal with fermented Lemna meal has not been able to provide good growth than P0 (0%), but the substitution of 10% addition has no effect on FCR and feed effisiency of red tilapia.